Traces of Defects in the Electronic Structure of Porous Ni-Ti Alloys - Ozkendir, O. M.; Cengiz, E.; Tirasoglu, E.; Kaya, Mehmet; Karahan, I. H.; Orhan, N. (Journal Mater Sci Technol, 2013)
The electronic structures of Ni-Ti shape-memory alloy samples were investigated by X-ray absorption fine structure (XAFS) spectroscopy both experimentally and theoretically. In the experimental section, the samples were measured at low temperature to determine the persistent traces of both preheating process and atomic concentration effects on the crystal and electronic structure by X-ray absorption near-edge structure (XANES) spectroscopy. As a second step, the extended-X-ray absorption fine structure (EXAFS) calculations, which are based on different choices of one electron potentials according to Ti coordinations by using the real space multiple scattering method FEFF 8.2 code, were performed. The crystallographic and electronic structures of the porous Ni-Ti alloys were tested at various temperatures ranging from 5 to 1323 K.
Keywords: Electronic structure; Porous Ni-Ti alloys; Shape memory effect; Transition metals